Analysis of the antimicrobial activity of zinc oxide nanoparticles against drug-resistant bacteria and their applications in the disinfection process - Dalia Alqaffaf; Ali M. Atoom; Rana Abu Huwaij; Mai Abdel Haleem A. Abusalah; Bayan Tayseer Alzubi; Awatef Al-Kaabneh; Manal Abdel Haleem A. Abusalah; Maher A. Sughayer (PLoS ONE, 2026)
Background The rise in antimicrobial resistance has necessitated the exploration of novel antimicrobial agents. Zinc oxide nanoparticles (ZnO-NPs) have gained prominence due to their biocompatibility, minimal toxicity, and potent antimicrobial properties. This study evaluates the antimicrobial activity of ZnO-NPs synthesized from Phoenix dactylifera root extract and their potential applications in disinfection. Methodology ZnO-NPs were synthesized using an eco-friendly method involving Phoenix dactylifera root extract and zinc acetate at varied concentrations and ratios, followed by annealing. The nanoparticles were characterized and assessed for antimicrobial activity against a spectrum of bacterial and fungal isolates using microtiter broth dilution, disc diffusion, and pour plate assays. Disinfection efficacy was evaluated on water samples and surfaces. Additionally, the impact of ZnO-NPs on acid-fast bacilli (AFB) isolates was examined using VersaTrek Mycobottles. Results ZnO-NPs exhibited potent antimicrobial activity against Gram-positive and Gram-negative bacteria, with minimum inhibitory concentrations (MICs) ranging from 9.7 to 310 µg/mL. Disc diffusion assays revealed larger inhibition zones in Gram-positive bacteria compared to Gram-negative strains, with MRSA showing the widest zone (24 mm). ZnO-NPs significantly reduced colony-forming units (CFU) on water and surfaces, achieving complete bacterial inhibition on laboratory benches within 20 minutes. The nanoparticles demonstrated bactericidal effects against AFB isolates, highlighting their broad-spectrum efficacy. Conclusion The study underscores the potential of ZnO-NPs as a versatile antimicrobial agent effective against MDR (multidrug-resistant) pathogens and environmental contaminants. Their rapid action and broad-spectrum activity make them suitable for disinfection in clinical and environmental settings. Future research could explore synergistic combinations with traditional antimicrobials to enhance efficacy against infections that are resistant to treatment.